IMPLEMENTATION OF SUPREME COURT REGULATION NUMBER 2 OF 2015 JUNCTO SUPREME COURT REGULATION NUMBER 4 OF 2019 CONCERNING PROCEDURES FOR SETTLEMENT OF SIMPLE LAWSUITS REGARDING THE TIME LIMIT FOR SETTLEMENT OF SIMPLE LAWSUITS IN THE PALANGKA RAYA DISTRICT COURT - Muhammad Dafi Nugraha; Yacob Ferdinan Martono; Evi; Louise Theresia (International Journal of Cultural and Social Science, 2026)
The purpose of this research is to analyze the implementation of the deadline for resolving simple lawsuits based on Supreme Court Regulation (Perma) No. 2 of 2015 juncto Perma No. 4 of 2019 concerning the Procedure for Resolving Simple Lawsuits at the Palangka Raya District Court and to identify the factors causing the deadline to be exceeded. This research adopts an empirical legal method with a descriptive qualitative approach thru interviews and case data analysis using the Case Tracking Information System (SIPP). The research results show that the majority of simple lawsuits are not resolved within the 25 working days timeframe, with some cases even lasting up to 618 days. The delays are caused by the absence of the parties, the low level of legal understanding in society, the lack of good faith from the defendant, administrative obstacles, and the absence of sanctions for exceeding the deadline. This condition indicates a gap between norms and practices, so the goal of a simple lawsuit as a mechanism for quick, simple, and low-cost dispute resolution has not yet been fully realized.